Organisasi Masyarakat Sipil Sumatera Barat Sebagai Kekuatan Politikdalam Proses Demokratisasi di Indonesia (Studi Kasus: Gugatan terhadap Undang-Undang Nomor 17 Tahun 2013) Tentang Organisasi Kemasyarakatan - Muhar Buyung, Tanaro (Dinasti Review Publisher, 2023)
Abstract: This study describes the process of the Draft Law being passed into Law No. 17 of 2013 concerning Community Organizations. To analyze the data found by researchers using the theoretical steps of Roem Topatimasang in his book entitled